PERLAKUAN PIUTANG TAK TERTAGIH PADA PT CDX SURABAYA - Jeremy Julio Wijaya (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2020)
Accounts receivable is part of the balance sheet that is in the current asset position, which arises as a result of a sale of goods, services or from a seller to the buyer, usually given a maturity of 30-90 days. Accounts receivable whose age exceeds 120 days will be included in the bad debts category. PT CDX is a trading company that has a material amount of receivables with a long collection period. This study intends to discuss the treatment of uncollectible accounts at PT CDX. This research was conducted using qualitative methods carried out through interviews, observation and primary data collection from PT CDX. The results of this study found that the accounts receivable turnover of PT. CDX is slow and the collection period for accounts receivable is also long. Where this shows that the cash obtained will also decrease from the end the cash flow that enters the company will also decrease and ultimately the company's cash flow is also ineffective. Management of accounts receivable at PT CDX that are still ineffective can be improved by giving a discount on each payment of receivables before maturity and a billing policy for accounts receivable before maturity and a firmer billing policy.